Huellas de un caminar no transitado. A propósito de una ética “en” Heidegger (2011)
The present essay does not pretend to do a research on the reasons why Heidegger did not write an ethical agreement, less an apology brings about his silence, intentionally or not, with regard to the above mentioned matter. This article does not pretend either to try to write an ethics “of” Heidegger, but rather, to find the signs that “let see” the ethical dimension of his thought and from there, take our thought through the way that leads usto the possibility of re-inhabiting the Earth.Keywords: Metaphysics, humanism, disclosedness, inhabit, guard, home, Earth.